Unseen Cinema - The Devil's Playing: American Surrealism Early American Avant-Garde Film 1894-1941 - Beheim, Eric; Israel, Robert; Sosin, Donald (image Entertainment, 2005)
Edwin S. Porter and other early filmmakers used bizarre sets, fantastic costumes, and magic lantern tricks to illuminate their fantasy films. American parody supplied Douglas Fairbanks with enough unusual material to produce the truly surreal "When the Clouds Roll By" (1919). The expressionistic "Cabinet of Dr. Calagari" (1919) influenced American sensibilities throughout the 1920s as seen in "Beggar of Horseback" (1925), "The Life and Death of 9413 - A Hollywood Extra" (1927) and "The Telltale Heart" (1928). The emphasis shifted when amateurs J.S. Watson, Jr., Joseph Cornell, and Orson Welles crafted a unique variety of American surrealism on film unfettered by European concerns. [Cover]
Keywords: DVD-Video